Kajian Fisiko Kimia dan Daya Terima Organoleptik Selai Nenas yang Menggunakan Pektin dari Limbah Kulit Kakao - Fahrizal Fahrizal; Rahmad Fadhil (Agricultural Faculty, 2014)
Cacao (Theobroma cacao) is one of the product commodities in Aceh and its production continues to increase every year. Parts of cocoa that have economic value are the seed, while the skin that is a waste of processing cocoa beans is often not utilized. Cocoa skin can cause environmental pollution problems. One way of handling waste is to extract cocoa skin becomes pectin. Known in the food industry pectin compounds is very important adjuvant because it is able to increase the viscosity of the fluid and form a gel with sugar and acid. The aim of this research was to determine the effect of pectin addition from cacoa skin waste on the quality of pineapple jam. There are four levels of the pectin addition in this study; 0, 0.5, 1.0 and 1.5%. Then the resulted pineapple jam was analysed; moisture content, total of dissolved solids, acidity, a smear of jam and hedonic sensory evaluation for appearance, aroma, flavor, texture and all vallue. The addition of pectin from cocoa waste have effects on moisture content, total of dissolved solids, pH value and a smear of jam of pineapple jam. In general, panelists like pineapple jam with the addition of 1% pectin from cocoa skin waste